Viewpoints about the Application of Nanoprobe Technology in Orthopedic Diseases Based on Its Functions in Disease Diagnosis and Treatment - Qi Yang; Fei Yu (Nano Biomedicine and Engineering)
Orthopedic diseases are common clinical disorders that impose a heavy burden on patients and their families, and they have presented considerable challenges to clinicians. Nanoprobes have emerged as a new microbial sensor technology with the advancement in nanotechnology. They can be employed to detect individual living cells, thus playing an important role in the diagnosis and treatment of diseases. Nanoprobes can target specific cells, subcellular organelles, exosomes, extracellular matrix, disease microenvironment, and metabolic products such as specific diagnostic substances and inflammatory factors produced in the progression of orthopedic diseases. Through the combination with photothermal, electromagnetic, ultrasound, and other excitation methods, they can achieve multidimensional targeted treatment for such orthopedic diseases as osteoarthritis, rheumatoid arthritis, malignant bone tumors, and bone fractures and defects by carrying drugs, proteins, peptides, and cytokines. Given these facts, the role of nanoprobe technology in the diagnosis and treatment of common orthopedic diseases is explored in this study.